The complete mitochondrial genome sequence of the greater wax moth Galleria mellonella (Insecta, Lepidoptera, Pyralidae): sequence and phylogenetic analysis comparison based on whole mitogenome. Issue 2 (12th December 2017) - Park, Yeong-Jun; Park, Chang Eon; Hong, Sung-Jun; Jung, Byung Kwon; Ibal, Jerald Conrad; Park, Gun-Seok; Shin, Jae-Ho
Abstract: The larva of Galleria mellonella is widely used as a model organism for in vivo toxicology and pathogenicity testing. Here, we report complete sequence of the mitochondrial genome (mitogenome) from G. mellonella, which is comprised of 15, 320 base pairs encoding 13 protein-coding genes, two ribosomal RNAs, 22 transfer RNAs, and an A + T rich region. The overall base composition was G + C: 19.6%, A + T: 80.4%, with an apparent AT bias. Phylogenetic analysis using whole mitogenome revealed that G. mellonella was closely related to Corcyra cephalonica, which is in the same Pyralidae family.